Understanding victimology: an active-learning approach - Clevenger, Shelly (Routledge, 2018)
Introduction to victimology -- Theories of victimization -- Victims' rights and remedies -- Hybrid and online victimization -- Personal and property victimization -- Rape, sexual assault, and kidnapping -- Intimate partner violence -- School and work victimization -- Victimization of special populations -- Hate crimes and terrorism